The dancing men - Doyle, Conan Arthur; Alex Woolf (London: Arcturus, 2022)
Join world-famous detective Sherlock Holmes and his ever-loyal sidekick Dr. Watson as they embark on a daring adventure. Hilton Cubitt is worried. Drawings of "dancing men" keep appearing around his house and they're frightening his wife, who seems to know what they mean. Can our brilliant hero solve the mystery of these drawings before disaster strikes? This thrilling tale has been retold and adapted with new illustrations, making it perfect for younger readers.